Diagnostic Accuracy Of Cytology And Colposcopy In Cervical Squamous Intraepithelial Lesion: A Four-Year Experience In Hospital University Sains Malaysia - Mohamed Tarmizi, Mohamed Hatta (2001)
To evaluate the diagnostic accuracy of cytology and colposcopy in women with cervical intraepitheliallesion using histology as the 'gold standard'. We aim to determine the sensitivity, specificity, positive and negative predictive values of cytology and/or colposcopy against histology in determining high-grade lesions. Secondly, to identify the possible risk factors for abnormal cytological smear of high-grade lesions in the population studied. STUDY DESIGN: A four-year cross sectional study from June 1997 to May 2001 was conducted in 112 women with abnormal cervical cytology who had undergone colposcopic examination in Hospital University Sains Malaysia. The correlation between cytology and colposcopic impression to colposcopically directed biopsy were analysed. The correlation was accepted accurate when both reports were either the same as histopathological diagnosis.